Zero-valent iron mediated degradation of sertraline - effect of H2O2 addition and application to sewage treatment plant effluent - de Lima Perini, João Angelo [UNESP]; Fernandes Pupo Nogueira, Raquel [UNESP] (Wiley, 2016)
BACKGROUND: Sertraline (SER) is a widely used antidepressant persistent in sewage treatment plant (STP) effluents. Zero-valent iron (ZVI) has been studied for degradation of organic contaminants. However, it usually results in poor mineralization efficiency. The effect of H2O2 on ZVI mediated degradation of SER was studied and compared with sole ZVI and the homogeneous Fenton process. RESULTS: The effect of ZVI dose on SER degradation was different with 20 and 200mesh particle sizes. The degradation rate was improved as the dose of larger particle (20mesh) was increased, while no significant variation was observed with smaller particle (200mesh). The SER degradation was hindered by the high Fe2+/H2O2 ratio as well as the sharp increase of pH when high ZVI doses or small particles were used. The addition of H2O2 (5mmolL-1) to the ZVI system greatly improved SER degradation and mineralization even at low ZVI dose (0.5gL-1). SER could be efficiently degraded in a STP effluent mediated by ZVI (20mesh), especially when H2O2 was employed. CONCLUSIONS: The potential of the ZVI/H2O2 process for degradation of SER in effluents from an STP was demonstrated, showing a significant improvement of target contaminant degradation and dissolved organic carbon (DOC) removal.
Keywords: Dechlorination; Fenton; Iron dissolution; Particle size; Wastewater treatment